Alkali activation of electric arc furnace slag: Mechanical properties and micro analyzes. (January 2019) - Ozturk, Murat; Bankir, Muzeyyen Balcikanli; Bolukbasi, Omer Saltuk; Sevim, Umur Korkut
Abstract: Research on sustainable concrete has drawn scientist's attentions on industrial by-products and wastes. Thus, consumption of raw materials would be diminished. In this study alkali activation of electric arc furnace slag (EAFS) was studied with a comprehensive test program. Different silicate modulus, sodium concentrations, curing conditions, curing temperatures and relative humidity condition variables were selected. Their effects on mechanical and micro structural behaviors of the mortar were investigated through SEM – XRD analyses. Result of this study, EAFS was activated with sodium hydroxide and sodium silicate solutions. Test results also revealed that increase in relative humidity, curing temperature and curing time had positive effects on strength parameters due to diminishing micro cracks and altering hydration reactions. With the current study utilization of EAFS is thought to be successfully disposed. Highlights: EAFS was activated with mixture of Na2 SiO3 and NaOH solutions on 72 different mixes. Micro structure of alkali activated EAFS is analyzed. Many different variables are considered which are effective in alkali activation like curing temperature, curing time, relative humidity, silicate modulus and sodium concentrations.